Narrating Crises of Trust in Post-Celtic Tiger Fiction - Katharina Rennhak (Diegesis: Interdisziplinäres E-Journal für Erzählforschung, 2023)
This article argues that post-Celtic Tiger fiction reflects the current crisis of trust and offers a perfect laboratory for the intersubjective negotiation of social practices of trust. Drawing on received and recent philosophical discussions of trust, the article first introduces the main parameters of this social phenomenon. Based on a corpus of about a dozen austerity novels, but with Donal Ryan’s The Spinning Heart (2012) as the main reference text, it then proceeds to establish (1) the general relevance of matters of trust for post-Celtic Tiger Fiction, and (2) the defining features of the narrative representation of social structures and performances of trust. Finally, in order to take into account not only trust-related issues and structures recurring in contemporary Irish austerity fiction, but to also point up pronounced differences in narrative form and ideological orientation among individual post-Tiger novels, it complements the reading of The Spinning Heart with an analysis of the narrative dynamics of ‘doing trust’ in Anne Enright’s The Forgotten Waltz (2011).